Exploring the Relationship between Transformational Leadership and Innovative Work Behavior: A Systematic Literature Review - Sueb Sueb; Sopiah Sopiah (Jurnal Visi Manajemen, 2023)
Transformational leadership encourages employees to take initiative, think creatively, and take risks in achieving organizational goals. The aim of this study is to provide an overview of transformational leadership and innovative behavior, explore the factors that mediate the relationship between transformational leadership and innovative behavior, and evaluate the influence of transformational leadership and innovative behavior by conducting a review of journals published in Scopus through "Publish or Perish" in the period 2017-2023. After conducting a systematic review using the PRISMA method, 31 relevant journals were found for this study. The search keywords used were "Transformational Leadership" and "Innovation Behaviour". The results of the study showed that transformational leadership is an important factor in promoting innovative work behavior. Several factors that mediate the relationship between transformational leadership and innovative behavior include organizational support for innovative behavior, innovation orientation and goal culture, meaningful work, digital literacy, team work quality, psychological empowerment, and motivation in general. In conclusion, transformational leadership has a significant impact on innovative work behavior.